Urgent Development on Contemporary Medical Fiqh in Malaysia - Noor Naemah Abdul Rahman; Mohd Anuar Ramli; Shaikh Mohd Saifudden Shaikh Mohd Salleh; Mohammad Naqib Hamdan (International Journal of Nusantara Islam, 2014)
The contemporary scientific and technology development give impacts on the development of Islamic law. The dynamic of fiqh in handling issues especially on medicine become a momentum of the synergy of the two diciplines, science and the Islamic jurisprudence of medicine. Many medical issuess are yet to require legal completions that are contemporary ijtihad based on perubatan discipline. On the other hand, ijtihad not only as exclusively unilateral, moreover inclusive multilateral approach (ijtihad jama’i) is needed on handling fiqh issues. It is because expert opinions also important in describing about those issuess. Without those opinions, Islamic law scholar could not give appropriate legal decision. However, this study will explore about the importance of development of Fiqh of Medicine based on contemporary ijtihad. These studies will explain some contemporary Medicine issuees, which is proof the requirement of contemporary ijtihad. For example on the issues of reproduktif organ donation. Some ijtihad instruments which are compatible will be aplicated based on the issuess. Research findings about perubatan issuess gave fact that there were not exact explanations on al-Qur’an and al-Sunnah also did not directly examined on fiqh book in the past. This condition cause contemporary ijtihad on those studies as an important study to give law answer about perubatan issues appear. Generally speaking, the current studies require the sinergized between the dynamic of Islamic law and the advance of science and technology.